A comparative study of clinical effects and recovery characteristics of intraoperative dexmedetomidine infusion with ketamine versus fentanyl as adjuvants in general anaesthesia - Mehershre Lodhi; Sulakshana Sulakshana; Anil P Singh; Bikram K Gupta (Indian Journal of Anaesthesia, 2023)
Background and Aims: Intraoperative dexmedetomidine infusion decreases the concurrent anaesthetic and analgesic requirement. However, because of slow onset and offset, it is often used with other drugs. Opioids have a depressant effect on the cardiorespiratory system while ketamine has the opposite pharmacodynamics. Hence, it was hypothesised that ketamine will have a better intraoperative haemodynamic profile compared to fentanyl. This study compared the clinical effects and recovery characteristics of ketamine versus fentanyl when used as an adjuvant along with dexmedetomidine infusion intraoperatively. Methods: A total of 80 patients (18-60 years) undergoing major surgeries were divided into two groups: Group (D + K) received an intraoperative infusion of ketamine 0.5 mg/kg/h, while group (D + F) received fentanyl 0.5 μg/kg/h along with intravenous dexmedetomidine 0.5 μg/kg/h. Intraoperative heart rate (HR), mean blood pressure, and oxygen saturation were recorded at 0 min, 10 min of induction, and thereafter every 30 min throughout the procedure. Ramsay sedation score (RSS) and visual analogue scale (VAS) score were measured at the end of the surgery, at 2 hours, 4 hours, and 6 hours. Results: Reduction in HR and mean blood pressure was more with a tendency of developing hypotension in the fentanyl group compared to the ketamine group. Post-anaesthesia care unit (PACU) stay, need for muscle relaxant and VAS score for pain were also significantly lesser in the ketamine group. Conclusion: Dexmedetomidine with ketamine provided better haemodynamic stability and reduced PACU stay compared to dexmedetomidine with fentanyl.